Active Surveillance Cultures and Procalcitonin in Combination With Clinical Data to Guide Empirical Antimicrobial Therapy in Hospitalized Medical Patients With Sepsis - Spoto, Silvia; Daniel Markley, John; Valeriani, Emanuele; Abbate, Antonio; Argemi, Josepmaria; Markley, Roshanak; Fogolari, Marta; Locorriere, Luciana; Anguissola, Giuseppina Beretta; Battifoglia, Giulia; Costantino, Sebastiano; Ciccozzi, Massimo; et al. (Frontiers in Microbiology, 2022)
Objective The prevalence of colonization with multidrug-resistant organisms (MDRO) has increased over the last decade, reaching levels as high as 23% in certain patient populations. Active surveillance cultures (ASC) represent a valuable tool to identify patients colonized with MDRO to apply preventive measures, reduce transmission, and guide empiric antimicrobial therapy. There is a paucity of data evaluating the impact of admission ASCs to predict future infection. The aim of this study was to evaluate the concordance between ASCs results and the development of clinical infection by the same microorganism identified in the surveillance swab (“swab-related infection”), in hospitalized septic patients, and to evaluate the presence of specific risk factors associated with the development of a swab-related infection. Methods All adults admitted to the Diagnostic and Therapeutic Medicine Department of the University Hospital Campus Bio-Medico of Rome with a diagnosis of infection or any other medical reason with admission surveillance swabs (rectal or nasal) between January 2018 and February 2021 were included in the study. A retrospective chart review was conducted to identify patients that developed infections with concordant MDROs identified on ASC, and the risk factors for swab-related infection. Secondary outcomes were need of intensive care unit transfer, length of stay, sepsis or septic shock development, and all-cause mortality. Results A total of 528 patients were included in the study, of which 97 (18.3%) had a positive surveillance swab. Among patients with positive surveillance swabs, 18 (18.5%) developed an infection with the same microorganism recovered from the swab, 57 (58.8%) developed an infection with a different microorganism than that recovered from the surveillance swab, and 22 (22.7%) did not develop an infection during hospitalization. The number of colonized sites, an interventional procedure within the previous 3 months, a Systemic Inflammatory Response Syndrome (SIRS) score ≥ 2, and a quick Sequential Organ Failure Assessment (q-SOFA) score ≥ 2 were associated with a significantly higher risk of developing a swab-related infection. SIRS and q-SOFA scores ≥ 2 and procalcitonin ≥ 0.43 ng/ml help for identifying patients with a swab-related infection. Conclusion Patients with positive surveillance swabs were at increased risk for development of infections by the same MDRO identified in surveillance swabs (swab-related infection). This study is the first to show that the positivity of surveillance swabs, in combination with anamnestic data, PCT values, and SIRS or q-SOFA scores, serves as a valuable tool to help clinicians predict patients at higher risk for swab-related infection development and guide the administration of appropriate empiric antimicrobial therapy in septic patients.